HILDCAA-related effects recorded in middle-low latitude magnetometers - Binod Adhikari (2015)
Disturbances of the geomagnetic field are caused by enhanced solar windmagnetosphere electrodynamical coupling process. The principal cause of geomagnetic disturbance is the magnetic reconnection between the southward directed interplanetary magnetic field component and the northward directed magnetopause field, that establishes an electrodynamic coupling between the solar wind plasma and magnetosphere. In general, this coupling is controled by dominant structures emanating from the sun like sporadic coronal mass ejections (CMEs) and their interplanetary counterparts (ICMEs), around the solar maximum, and by corotating high-speed streams, including corotating interaction region (CIR), in the descending and minimum phases of solar cycle. These high speed streams are embedded with highly fluctuating Alfven waves, which produce phenomena called HILDCAA events (high-intensity, long duration, continuous AE activity). This study investigates magnetic records from middle-low latitude geomagnetic observatories during HILDCAA periods. To this purpose, three primary conditions of the interplanetary space are considered: HILDCAA (i) not preceded by magnetic storm, (ii) preceded by storm generated by CIR, and (iii) preceded by storm generated by ICME. A fourth case is considered as a background condition: a geomagnetically quiet interval. As methodology of analysis, wavelet techniques to study multi-scale features of the HILDCAA events were explored in this work. The signal analyses techniques are composed by continuous wavelet transform, discrete wavelet transform, cross correlation using wavelet, and the usual modulus cross correlation. Complementarly, an evaluation on the field aligned currents (FAC) are considered in the investigation. Besides this, we estimate the polar cap potential (PCP) and merging electric field (Ey), and examine the role of PCP and geomagnetic AL index to monitor geomagnetic activity generated by geoeffective solar wind parameters during HILDCAAs. Thus, this work contributes to extend the understanding of HILDCAA events at higher latitudes to disturbances occurring at middle-low latitudes. There are magnetic effects related to the occurrence of HILDCAA even at middle-low latitudes.